2008
DOI: 10.1111/j.1600-0420.2007.01010.x
|View full text |Cite
|
Sign up to set email alerts
|

The relaxing effect of perivascular tissue on porcine retinal arterioles in vitro is mimicked by N‐methyl‐D‐aspartate and is blocked by prostaglandin synthesis inhibition

Abstract: ABSTRACT.Purpose: Retinal hyperperfusion resulting from disturbances in the regulation of arteriolar tone is involved in the pathophysiology of a variety of retinal diseases. The mechanisms underlying this regulation of tone involve cellular components in both the vascular wall and the perivascular tissue. However, previous in vitro studies of the influence of perivascular retinal tissue on retinal tone regulation have been hampered by the release of an endogenous relaxing factor that renders the arteriole ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 23 publications
(28 reference statements)
2
31
0
Order By: Relevance
“…Excessive stimulation of these glutamate receptors has been shown to play a role in the pathologic course of various neurodegenerative diseases, including retinal ischaemia (Louzada-Junior et al 1992), diabetic retinopathy (Kowluru et al 2001), optic nerve ischaemia (Kim et al 2000), and stroke and epilepsy (Lipton & Rosenberg 1994). In RGCs, glutamate toxicity is primarily mediated by NDMA receptors (Sun et al 2001;Calzada et al 2002;Holmgaard et al 2008;Teuchner et al Neuroprotective effect of epigallocatechin-3-gallate against N-methyl-d-aspartateinduced excitotoxicity in the adult rat retina (Sun et al 2001;Ju et al 2009). Epigallocatechin-3-gallate (EGCG) is a powerful antioxidant exhibiting multifunctional properties including anti-inflammatory and antiapoptotic effects and has shown neuroprotective effects in vivo and in vitro studies (Sutherland et al 2006;Zhang et al 2007Zhang et al , 2008Peng et al 2008;Osborne 2009;Xie et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Excessive stimulation of these glutamate receptors has been shown to play a role in the pathologic course of various neurodegenerative diseases, including retinal ischaemia (Louzada-Junior et al 1992), diabetic retinopathy (Kowluru et al 2001), optic nerve ischaemia (Kim et al 2000), and stroke and epilepsy (Lipton & Rosenberg 1994). In RGCs, glutamate toxicity is primarily mediated by NDMA receptors (Sun et al 2001;Calzada et al 2002;Holmgaard et al 2008;Teuchner et al Neuroprotective effect of epigallocatechin-3-gallate against N-methyl-d-aspartateinduced excitotoxicity in the adult rat retina (Sun et al 2001;Ju et al 2009). Epigallocatechin-3-gallate (EGCG) is a powerful antioxidant exhibiting multifunctional properties including anti-inflammatory and antiapoptotic effects and has shown neuroprotective effects in vivo and in vitro studies (Sutherland et al 2006;Zhang et al 2007Zhang et al , 2008Peng et al 2008;Osborne 2009;Xie et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Our results were obtained under constant flow conditions, which are expected to modulate arterial diameter through endothelial mechanisms from the vascular wall [20], through myogenic response secondary to stretch-induced reactions [11,21], and probably also from the perivascular tissue [22].…”
Section: Discussionmentioning
confidence: 95%
“…RRF, from the perivascular retinal tissue which displayed different relaxing characteristics from the well known mediators of retinal circulation. Besides, subsequent in vitro studies established that glutamate receptor agonist, N-methyl-D-aspartate (NMDA) can mimic the inhibitory influence of perivascular tissue on the contractility of the retinal artery and else, NMDA as well as ATP can produce relaxations on retinal arteries which depend on the presence of perivascular retinal tissue (Holmgaard et al, 2007(Holmgaard et al, , 2008a(Holmgaard et al, , 2008b Therein, the underlying inhibitory influence was found to be related to adenosine but not to RRF. Although, adenosine was recently suggested to interfere with RRF in the retinal tissue to produce much prominent relaxations in the retinal artery (Maenhaut et al, 2009), the relaxing mechanisms of RRF still remain undefined.…”
Section: Discussionmentioning
confidence: 96%
“…The local regulation of the retinal microcirculation has been shown to depend on several compounds released from either the retinal tissue or the endothelium of the retinal artery, including nitric oxide (NO), prostaglandins, and ATP/adenosine (Holmgaard et al, 2007(Holmgaard et al, , 2008a(Holmgaard et al, , 2008bPournaras et al, 2008). Previous studies have reported that a novel factor, named as retinal relaxing factor (RRF), is released from the retinal tissues of different species and likely to contribute to the maintenance of retinal arterial tone (Delaey and Van de Voorde, 1998;Boussery et al, 2002aBoussery et al, , 2002b.…”
Section: Introductionmentioning
confidence: 96%